see the picture answer it
Attachments:
![](https://hi-static.z-dn.net/files/ddf/4dfd356eb8878fd5d7890d436e25c80f.jpg)
Answers
Answered by
3
heya
here is ur answer
here is ur answer
Attachments:
![](https://hi-static.z-dn.net/files/dbf/153b9cf2ff4ddf7ab56824e4e63cfd03.jpg)
Answered by
4
Answer:
θ + ∅ = π/4
Step-by-step explanation:
Given : tan θ = 5/6 and tan ∅ = 1/11.
We know that tan(A + B) = (tanA tanB)/(1 - tan A tanB)
⇒ tan(θ + ∅) = (tan θ + tan∅)/1 - tan θ tan ∅
= (5/6 + 1/11)/1 - (5/6)(1/11)
= (61/11)/(61/11)
= 1.
So, tan(θ + ∅) = 1
⇒ tan(θ + ∅) = tan 45°
⇒ θ + ∅ = π/4.
Hope it helps!
Similar questions